Pattern of aerobic bacteria with antimicrobial susceptibility causing community acquired urinary tract infection (Mymensingh Medical Journal, 2009)
Mymensingh Med J. 2009 Jul;18(2):148-53.The abstract of this article is available on the PubMed website